A társadalmi mobilitás lehetőségei a Horthy-korszak felsőoktatási rendszerében - Sándor, Király (Gerundium, 2015)
POSSIBILITIES OF SOCIAL MOBILITY IN THE HIGHER ADUCATION SYSTEM OF THE HORTY-ERA. he living circumstances of academic students were always determined by the prosperity of their parents. he income of parents in prestigous positions with higher qualiications provided for the education of their children, in an era when high expenses deined education as a privilege for a narrow social strata. By the beginning of the 20th century, the democratization of the higher education, the apperance of women and students from lower social strata at the universities had become an international tendency. he increasing number of students in Hungary was also due to the WWI. As students came from various social backgrounds, they received an opportunity to socially rise through education. he study aims at identifying the processes behind the social mobility of academic students between the two WWs.